2016
DOI: 10.18632/oncotarget.14117
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy inhibition enhances photocytotoxicity of Photosan-II in human colorectal cancer cells

Abstract: Photodynamic therapy (PDT) has emerged as an attractive therapeutic treatment for colorectal cancer because of its accessibility through endoscopy and its ability to selectively target tumors without destroying the anatomical integrity of the colon. We therefore investigated the therapeutic relevance of the interplay between autophagy and apoptosis in Photosan-II (PS-II)-mediated photodynamic therapy (PS-PDT) in in vitro and in vivo models for human colorectal cancer. We observed that PS-PDT-induced dose-depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 49 publications
0
28
1
Order By: Relevance
“…PDT studies with porphyrin IX in HCT116 colon cancer cells reported that inhibition of autophagy was effective for PDT antitumor effects (32). In a study of sinoporphyrin sodium mediated PDT and photosan-II mediated PDT applied to human colorectal cancer cells, autophagy inhibition increased the efficacy of PDT (33,34). In our study, overexpression of p62, which plays an important role in autophagy, increased the effect of PDT, conflicting with previously reported studies.…”
Section: Discussioncontrasting
confidence: 99%
“…PDT studies with porphyrin IX in HCT116 colon cancer cells reported that inhibition of autophagy was effective for PDT antitumor effects (32). In a study of sinoporphyrin sodium mediated PDT and photosan-II mediated PDT applied to human colorectal cancer cells, autophagy inhibition increased the efficacy of PDT (33,34). In our study, overexpression of p62, which plays an important role in autophagy, increased the effect of PDT, conflicting with previously reported studies.…”
Section: Discussioncontrasting
confidence: 99%
“…celecoxib and an antagonist of Bcl-2/Bcl-xL [ 26 ], PI3K/mTOR inhibitor [ 27 ], BRAF inhibitor [ 28 ], niacin and tumor necrosis factor-related apoptosis-inducing ligand [ 29 ], store-operated Ca 2+ entry inhibitor [ 30 ], SN-38/CPT-11 [ 31 ]), other compounds or extracts (e.g. icaritin [ 32 ], tetrandrine [ 33 ], apigenin [ 34 ], purvalanol [ 35 ]), radiation therapy [ 36 ] and photodynamic therapy [ 37 ]. Moreover, endoplasmic reticulum (ER) stress appears to be a crucial intermediate event as inhibition of ER stress has been found to suppress autophagy and subsequently enhance apoptosis in sodium butyrate-treated CRC cells [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Autophagy is a lysosomal-dependent degradation process induced under various conditions or stresses [ 29 ]. Autophagy is reported as an alternative molecular mechanism by which the cell death is induced [ 30 ].…”
Section: Introductionmentioning
confidence: 99%